1998
DOI: 10.1111/j.1399-0039.1998.tb02973.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA haplotypes in Koreans based on 107 families

Abstract: There are marked differences in the distribution of HLA haplotypes among different populations, and multilocus HLA haplotypes can best be studied by family analysis In the present study, 107 Korean families were analyzed for HLA-A, B, C, DR, and DQ antigens and haplotypes. Allele frequencies of more than 10% for class I antigens were A2. A24, A33, B44, B62, Cwl, Cw7, Cw9, CwlO, and C blank (CBL) and those for class II antigens were DR4, DR8, DR13, DR15. DQ1, DQ3, DQ4 and DQ7. In the analysis of HLA haplotypes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…On the other hand, the protective effect of HLA-DRB1*13 against SARS found in our study might be rather weak and, for the time being, difficult to be supported by other studies, although this association itself is interesting because HLA-DRB1*13 has been reported to play a protective role in HBV infection [15,16] and malaria [17]. The possibly resistant allele, HLA-DRB1*13 is also one of the characteristic alleles in the Korean and Japanese population that did not experience SARS [18].…”
Section: Discussioncontrasting
confidence: 69%
“…On the other hand, the protective effect of HLA-DRB1*13 against SARS found in our study might be rather weak and, for the time being, difficult to be supported by other studies, although this association itself is interesting because HLA-DRB1*13 has been reported to play a protective role in HBV infection [15,16] and malaria [17]. The possibly resistant allele, HLA-DRB1*13 is also one of the characteristic alleles in the Korean and Japanese population that did not experience SARS [18].…”
Section: Discussioncontrasting
confidence: 69%
“…It should be noted that the favorable outcomes of HLAhaploidentical HCT in our study were observed in Korean patients, an ethnic population with a low level of HLA-gene heterogeneity 30 and that experiences less GVHD after HLA-matched HCT. 31,32 Hence, further clinical studies are necessary to ascertain whether our results can be extended to patients of other countries.…”
Section: Discussionmentioning
confidence: 97%
“…These epitopes overlap with each other to form four specific regions within the HBV core protein (HBcAg), encompassing amino acid (aa) residues 11–27, 88–96, 107–125, and 139–151. The HLA haplo-types recognizing these epitopes are all found in the Korean population [Park et al, 1998]. To evaluate sequence changes, a consensus nucleotide sequence for all subject sequences was generated using Geneious Pro software (Biomatters), and sequences from individuals were then compared to this consensus sequence and nucleotide mutations were noted.…”
Section: Methodsmentioning
confidence: 99%